Peran Bank Indonesia dalam Perlindungan Perbankan - Dea Nurhanifah; Ari Maulana; Aria Dwi Fahrezi; Farid Chaidar Pasya (Universitas Sains dan Teknologi Komputer, 2024)
This research explores the role of Bank Indonesia in banking protection in Indonesia. Through the analysis of policies and regulations applied by Bank Indonesia, this research aims to understand how the institution contributes to maintaining the stability and security of the banking sector. The findings of this research illustrate that Bank Indonesia not only acts as a monetary authority, but also has a crucial role in supervising, regulating, and protecting banking institutions from systemic risks. The implication of this role can be felt in an effort to maintain public trust in the national banking system and increase overall economic resilience.